The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1038/nrn2099
|View full text |Cite
|
Sign up to set email alerts
|

Repair of neural pathways by olfactory ensheathing cells

Abstract: Damage to nerve fibre pathways results in a devastating loss of function, due to the disconnection of nerve fibres from their targets. However, some recovery does occur and this has been correlated with the formation of new (albeit abnormal) connections. The view that an untapped growth potential resides in the adult CNS has led to various attempts to stimulate the repair of disconnectional injuries. A key factor in the failure of axonal regeneration in the CNS after injury is the loss of the aligned glial pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
129
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(130 citation statements)
references
References 170 publications
0
129
0
1
Order By: Relevance
“…This remarkable regenerative property of the olfactory system is thought to be in part due to a special type of glia cells [2,3], the olfactory ensheathing cells (OECs), which support and guide the growth of olfactory axons and ensheath the bundles of olfactory nerves that extend from the olfactory epithelium to the olfactory bulb [4]. Owing to these unique roles, OEC transplantation has emerged as a promising experimental therapy for axonal injuries and demyelinating disease [5]. Experimental studies have shown that OECs transplanted near nerve injury sites can not only promote the re-growth of injured axons [6][7][8], but also form myelin sheaths around demyelinated axons, leading to the restoration of axonal functions [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This remarkable regenerative property of the olfactory system is thought to be in part due to a special type of glia cells [2,3], the olfactory ensheathing cells (OECs), which support and guide the growth of olfactory axons and ensheath the bundles of olfactory nerves that extend from the olfactory epithelium to the olfactory bulb [4]. Owing to these unique roles, OEC transplantation has emerged as a promising experimental therapy for axonal injuries and demyelinating disease [5]. Experimental studies have shown that OECs transplanted near nerve injury sites can not only promote the re-growth of injured axons [6][7][8], but also form myelin sheaths around demyelinated axons, leading to the restoration of axonal functions [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…18 Full explanation is not only far beyond the scope of this report but also unavailable based on existing scientific data. Raisman and colleagues 19,20 are working on using olfactory ensheathing cells to overcome the barrier after spinal cord injury. It is a task of further intensive and extensive research for a long time to come.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, these new axons can regenerate SNGs only by accessing their tip, whereas the remaining SNGs are covered by epineurium that is impenetrable for neuronal buds. Newly formed myelinated axons were observed in various areas of the SC, including Rexed laminae (Rxl) [1][2][3][4][5][6][7][8][9][10]. The Rexed laminae comprise a system of ten layers of gray matter (I-X), which is identified by Bror Rexed to label portions of the gray columns of the spinal cord (Figures 8 and 9), the lateral funiculus (lf), the lateral spinal nucleus (LSp), the rubrospinal (rs) tract, the medullary (caudal) reticulospinal (mrs) tract, the dorsal corticospinal (dcs) tract, the gracile fascicle (gr), the lumbar dorsal common (LDCom), and the postsynaptic dorsal column (psdc).…”
Section: Axon Regeneration and Sproutingmentioning
confidence: 99%
“…To date, traumatic paraplegia by severance of the spinal cord (SC) remains an irreversible functional clinical condition [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation